2004
DOI: 10.1002/bse.390
|View full text |Cite
|
Sign up to set email alerts
|

The impact of voluntary environmental protection instruments on company environmental performance

Abstract: In the last decade there has been increasing emphasis on the use of voluntary environmental protection tools such as corporate environmental reporting (CER) and environmental management systems (EMS). There has been relatively little research, however, on the impact of these tools on the actual environmental performance of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 30 publications
7
73
1
2
Order By: Relevance
“…Our findings coincide with those derived from previous research (e.g. Annandale et al, 2004;Melnyk et al, 2003;Zhu and Sarkis, 2004). In fact, Wagner (2005) also demonstrates that high levels of environmental performance are only possible if a firm's environmental management has a proactive technological pollution orientation.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings coincide with those derived from previous research (e.g. Annandale et al, 2004;Melnyk et al, 2003;Zhu and Sarkis, 2004). In fact, Wagner (2005) also demonstrates that high levels of environmental performance are only possible if a firm's environmental management has a proactive technological pollution orientation.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 91%
“…Environmental management and environmental performance The environmental management literature has shown that the adoption of environmental practices by firms typically leads to or has to do with good environmental performance (e.g. Annandale et al, 2004;Melnyk et al, 2003;Zhu and Sarkis, 2004).…”
Section: Early Moving and Environmental Managementmentioning
confidence: 99%
“…Corporate environmental managers have been surveyed on environmental reporting practices, focusing for example on the determinants of corporate environmental disclosures , on the influence of such disclosures on corporate environmental performance (Annandale et al, 2004), on the development of environmental policies in companies (Tilt, 1997), and on the media channels used to disseminate environmental information (Stray and Ballantine, 2000). Other studies have investigated financial determinants of reporting activities (Cormier and Magnan, 2003) and the relationship between corporate financial performance and environmental reporting efforts (Connelly and Limpaphayom, 2004;Stanwick and Stanwick, 2000).…”
Section: Corporate Environmental Reportingmentioning
confidence: 99%
“…Several researchers have discussed mandatory and voluntary environmental management initiatives in order to reduce negative corporate environmental impacts [5][6][7][8][9]. Among the voluntary initiatives that should improve organizational environmental performance beyond the legal requirements is the implementation of an environmental management system (EMS) [9,10].…”
Section: Introductionmentioning
confidence: 99%